Putting people and robots together in manufacturing: are we ready? - Fletcher, Sarah R.; Johnson, Teegan L.; Larreina, J. (Unknown, 2017)
Traditionally, industrial robots have been completely segregated from people in manufacturing systems to mitigate the dangers posed by their operational speeds and heavy payloads. Putting human operators together with large-scale industrial robots is now becoming increasingly possible with the development of integrated safety monitoring systems, and with smaller force-limited robotics that are now being produced with sufficient robustness for industry. However, with long-standing perceptions of robots as hazardous, we do not yet know how manufacturing workforces will accept collaborative systems with either large or small scale robotics and there is a need to identify and define new ethical and safety standard requirements for integrating people and robots to work collaboratively in industrial assembly tasks. To date there is little or no attention to ethical issues or psychological safety in the industrial safety standards that govern robotics and automated work systems. This paper describes the current situation and specific ways in which human-robot collaboration will significantly improve efficiency and flexibility, and outlines some early work that is being performed to identify the requirements that will be needed in order to facilitate this new way of bringing people and robots together in manufacturing. It presents a brief summary of initial findings that support the need for ethical issues to be considered as a candidate for new and / or revised safety standards.
Keywords: advanced manufacturing technology; industrial robots; human-robot collaboration; industrial safety